2000
DOI: 10.2214/ajr.174.6.1741769
|View full text |Cite
|
Sign up to set email alerts
|

Breast Imaging Reporting and Data System

Abstract: Inter- and intraobserver variability in mammographic interpretation is substantial for both feature analysis and management. Continued development of methods to improve standardization in mammographic interpretation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(93 citation statements)
references
References 29 publications
9
80
3
1
Order By: Relevance
“…The moderate inter-reader agreement for the morphology and distribution of microcalcifications seen in this study has previously been described for mammography [14] and tomosynthesis [3]. We found that this also holds true for INSIGHT3D without significant differences with respect to SM or the standard stack reconstruction.…”
Section: Discussionsupporting
confidence: 84%
“…The moderate inter-reader agreement for the morphology and distribution of microcalcifications seen in this study has previously been described for mammography [14] and tomosynthesis [3]. We found that this also holds true for INSIGHT3D without significant differences with respect to SM or the standard stack reconstruction.…”
Section: Discussionsupporting
confidence: 84%
“…At the present time, this classification is a primarily subjective estimate of quartiles from almost entirely fat, to extremely dense. There is marked inter observer variability between radiologists (28, 29), raising concern for integrating this information into clinical use.…”
Section: Automated Breast Densitymentioning
confidence: 99%
“…16, 30 Subjectively rating mammographic density based on the BIRADS standard is often not accurate or reliable due to the large intra- and inter-reader variability. 3 In addition, many useful mammographic density features, such as tissue spiculation patterns and bilateral asymmetry cannot be quantitatively evaluated and compared using subjective (visual) assessment.…”
Section: Introductionmentioning
confidence: 99%